Equity valuation : Apple Inc - Ferreira, Francisco Seixas do Val (2019)
In the following dissertation, a valuation of Apple Inc is completed. Apple is an American multinational technology company, that designs and develops electronic products, software, among others. Three valuation techniques were applied – Discounted Cash Flows using WACC, Dividend Discount Model and Relative Valuation – after which a sensitivity analysis was conducted. The share prices achieved were 209.7$ for Discounted Cash Flows approach, 67.3$ for the Dividend Discount Model, 280.7$ for the Relative Valuation using Price-Earnings, 262.1$ for the Relative Valuation using EV/EBITDA and 284.2$ for the Relative Valuation using EV/EBIT. Thus, an Outperform recommendation was given. DDM turned out to be irrelevant for the case of Apple as well as the Relative Valuation which, although it inherently conveys market perceptions, will work only a validation tool. Hence, no recommendations arose from both methods. Lastly, a comparison between these results and an Equity Research Analyst Report from JP Morgan was made, where the main differences between the two were highlighted.